Uniformly-distributed defect-free c-PIMs / MOFs composite membrane as well as preparation method and application thereof

The solvent evaporation method addresses the agglomeration and compatibility issues of MOFs in PIMs matrices by creating a nano-confined space, resulting in a uniformly distributed composite membrane with enhanced gas separation performance and stability.

CN119236719AActive Publication Date: 2025-01-03DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411495503.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-03
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The agglomeration and poor interfacial compatibility of MOFs nanoparticles in PIMs matrices lead to non-selective voids and holes in membranes, affecting gas separation performance.

Method used

A solvent evaporation method is used to prepare a uniformly distributed defect-free PIMs/MOFs composite membrane by constructing a nano-confined space through heat treatment, regulating MOFs growth, and enhancing interface compatibility.

Benefits of technology

The method results in a composite membrane with good interface compatibility and high gas selectivity, improving gas separation performance and long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236719A_ABST
    Figure CN119236719A_ABST
Patent Text Reader

Abstract

The invention discloses a uniformly-distributed defect-free c-PIMs / MOFs composite membrane as well as a preparation method and application thereof, and belongs to the technical field of gas separation membrane technology separation. The MOFs / PIMs composite membrane is a homogeneous membrane and comprises a modified PIMs matrix and MOFs nanoparticles, the MOFs nanoparticles are uniformly embedded into the modified PIMs matrix, and the MOFs / PIMs composite membrane is formed by compounding a modified PIMs chain segment structure and a MOFs / PIMs cross-linked structure; the PIMs matrix in the composite membrane has continuous cavities, and the MOFs have regular pore channels. Firstly, a modified polymer PIMs is prepared; secondly, preparing an MOFs seed crystal solution; and finally, carrying out heat treatment on the PIMs / MOFs membrane casting solution through a solvent evaporation method to prepare the c-PIMs / MOFs composite membrane. On the basis of the concept of solvent volatilization, the gas separation performance and long-term stability of the PIMs composite membrane are improved by optimizing solvent volatilization conditions and regulating and controlling the interfacial compatibility between PIMs and MOFs; the interfacial compatibility between PIMs-MOFs can be improved, non-selective defects are avoided, and formation of a defect-free composite membrane is promoted; selective rapid transfer of gas can be achieved, and preparation of the evenly-distributed defect-free composite membrane is further achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas separation membrane separation, and relates to a method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane. The obtained c-PIMs / MOFs cross-linked membrane can be used for, but is not limited to, a gas separation system. Background Art

[0002] As global climate change intensifies, carbon dioxide (CO2) capture and storage (CCS) technology has received increasing attention. Industrial production and energy consumption are the main sources of CO2 emissions, and the development of efficient CO2 capture technology has become an important measure to address climate change. Membrane separation technology is more attractive than traditional chemical absorption methods due to its advantages such as low energy consumption, simple operation and environmental friendliness. In particular, self-polymerized microporous polymer membranes (PIMs) have become a research hotspot because their gas permeability is much higher than that of commercial polymer membranes.

[0003] In the process of improving the performance of PIMs membranes, incorporating nanofillers into the PIMs matrix to prepare mixed matrix membranes (MMMs) is an effective strategy to combine the excellent selectivity of nanofillers and the high gas permeability of PIMs. Metal organic frameworks (MOFs) exhibit excellent selectivity in gas separation due to their advantages such as adjustable pore size, highly porous structure and controllable chemical composition. However, the agglomeration and deposition of MOFs nanoparticles and their poor interfacial compatibility with the PIMs matrix lead to the generation of non-selective voids and holes in the membrane, which seriously affect the gas separation performance of the membrane. To this end, researchers have proposed a variety of methods such as adjusting the surface chemical properties of MOFs, using interfacial agents and geometric regulation of MOFs. However, achieving uniform dispersion of high-load MOFs in the PIMs matrix remains a difficult problem.

[0004] In order to solve the above problems, the present invention adopts a solvent evaporation method to prepare a uniformly distributed defect-free PIMs-MOFs mixed matrix membrane. The PIMs-MOFs casting solution is subjected to heat treatment, and the growth environment of MOFs is regulated by constructing a nano-confined space in the membrane. This method will optimize the distribution of MOFs nanoparticles in the PIMs polymer matrix and improve the interface compatibility between PIMs and MOFs, thereby improving the gas separation performance of the PIMs membrane. Summary of the invention

[0005] The present invention aims to provide a uniformly distributed defect-free c-PIMs / MOFs composite membrane, solving the problem that it is difficult to prepare a high-performance aging-resistant PIMs membrane in the prior art. At the same time, a method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane is provided, characterized in that a defect-free gas selective permeation structure in the c-PIMs / MOFs composite membrane is constructed by a solvent volatilization method. The preparation process is simple to operate, and a c-PIMs / MOFs composite membrane with good interface compatibility and high gas selectivity can be obtained.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0007] A uniformly distributed defect-free c-PIMs / MOFs composite membrane, the composite membrane is a homogeneous membrane, including a modified PIMs matrix and MOFs nanoparticles, wherein the MOFs nanoparticles are uniformly embedded in the modified PIMs matrix, and specifically composed of a modified PIMs segment structure, and a MOFs and PIMs cross-linked structure. In the composite membrane, the continuous cavities in the PIMs matrix and the regular pores in the MOFs serve as gas selective transmission channels, the PIMs matrix and the MOFs nanoparticles have excellent interface compatibility, and the composite membrane has good gas separation performance and long-term stability.

[0008] Furthermore, the thickness of the c-PIMs / MOFs composite membrane material is 50-150 μm.

[0009] A method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane material, wherein the preparation method first prepares modified polymer PIMs. Secondly, a MOFs seed solution is prepared. Finally, the PIMs / MOFs casting solution is heat-treated by a solvent volatilization method to construct a confined space between polymer chains to regulate the growth space and distribution state of MOFs, thereby preparing a c-PIMs / MOFs composite membrane. The formula of the casting solution of the composite membrane contains modified PIMs, MOFs nanoparticles and a solvent; wherein the molar concentration ratio of the metal salt of the MOFs nanoparticles to the PIMs is 0.05 to 1. The method comprises the following steps:

[0010] Step 1: Preparation of modified polymer PIMs;

[0011] Step 1.1) Preparation of polymer PIM-1: Under nitrogen (N2) atmosphere, the reaction monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane (TTSBI) is dissolved with tetrafluoroterephthalonitrile (TFTPN) and anhydrous potassium carbonate (K2CO3) in solvent A, and the mixture is poured into a three-necked flask and reacted at a temperature of 65-160°C for 0.5-72h. The reaction mechanism of this step is: the aromatic tetraol monomer TTSBI and the fluorine-containing compound TFTPN undergo aromatic nucleophilic substitution reaction under the catalysis of K2CO3 to form a high molecular weight soluble microporous polymer PIM-1. After the reaction is completed, the solution is cooled to room temperature and gradually poured into methanol to precipitate a fluorescent yellow solid. The obtained solid is dissolved in chloroform, and the solution is poured into methanol again for precipitation to obtain a polymer solid. This process is repeated many times to ensure the purity and high molecular weight of the polymer. The filtered polymer solid was poured into deionized water and stirred at 100° C. for 4 h to completely remove the residual K 2 CO 3 . The collected yellow polymer was vacuum dried to obtain polymer PIM-1.

[0012] Step 1.2) preparing modified polymer PIMs;

[0013] The polymer PIM-1 obtained in step 1.1) is dissolved in solvent B under N2 atmosphere, and then the modified solution A is added to the reaction solution and refluxed at 25-155°C for 0.5-72h. After cooling to room temperature, the mixture is poured into solvent C and filtered to obtain a light yellow powder. The polymer product is washed with 500mL of ethanol for multiple times and then vacuum dried to obtain a modified polymer PIMs.

[0014] In the step 1.1), 4-8 g TFTPN and 6.91-13.82 g K2CO3 are added for every 7.36 g TTSBI. The vacuum drying temperature is 60-120° C. and the drying time is 24-72 h.

[0015] In the step 1.1), the solvent A is one of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide.

[0016] In the step 1.2), the solvent B is one of tetrahydrofuran, deionized water, and dichloromethane; the solvent C is one or more of deionized water, methanol, and ethanol.

[0017] In the step 1.2), the modified solution A is one of hydroxylamine aqueous solution, concentrated sulfuric acid, and chlorosulfonic acid.

[0018] In the step 1.2), the modified polymer PIMs is one of amidoximated PIMs (AOPIM-1), carboxylated PIMs (PIM-COOH), and sulfonated PIMs (SPIM-1).

[0019] When solvent B is tetrahydrofuran and modification solution A is aqueous hydroxylamine solution, the modified PIMs obtained are AOPIM-1; when solvent B is deionized water and modification solution A is concentrated sulfuric acid, the modified PIMs obtained are PIM-COOH; when solvent B is dichloromethane and modification solution A is chlorosulfonic acid, the modified PIMs obtained are SPIM-1.

[0020] Step 2: Prepare MOFs seed solution;

[0021] Step 2.1) At room temperature, a metal salt is added to solvent D, and a uniform metal salt solution is formed by ultrasound at room temperature to prepare a metal salt dispersion with a concentration of 0.05 to 3 g / L; an organic ligand is added to solvent E, and a uniform organic ligand solution is formed by ultrasound at room temperature to prepare an organic ligand dispersion with a concentration of 0.05 to 36 g / L.

[0022] Step 2.2) Mix the metal salt dispersion and the organic ligand dispersion obtained in step 2.1), pour the reaction mixture into a three-necked flask, heat at 30-140°C for 2-24 hours, and cool naturally to room temperature to obtain a MOFs seed solution. For every 3 mL of the metal salt dispersion, 3-60 mL of the organic ligand dispersion is added.

[0023] In the step 2.1), the solvent D is one of N,N-dimethylformamide, N-methylpyrrolidone and chloroform, and the solvent E is one of N,N-dimethylformamide, N-methylpyrrolidone and chloroform.

[0024] In the step 2.1), the metal salt is one of zinc nitrate hexahydrate, zirconium chloride, and copper nitrate trihydrate. The organic ligand is one of imidazole dicarboxaldehyde, 2-aminoterephthalic acid, and trimesic acid.

[0025] In the step 2.2), the MOFs in the obtained seed solution is one of ZIF-90, UiO-66-NH2, and HKUST-1. When the metal salt is zinc nitrate hexahydrate and the organic ligand is imidazole dicarboxaldehyde, the obtained MOFs is ZIF-90; when the metal salt is zirconium chloride and the organic ligand is 2-aminoterephthalic acid, the obtained MOFs is UiO-66-NH2; when the metal salt is copper nitrate trihydrate and the organic ligand is trimesic acid, the obtained MOFs is HKUST-1.

[0026] Step 3: Preparation of c-PIMs / MOFs composite membrane;

[0027] The c-PIMs / MOFs composite membrane was thermally treated by solvent evaporation method as follows:

[0028] Under N2 atmosphere, the MOFs seed solution obtained in the second step and the modified polymer PIMs obtained in the first step are dissolved in solvent F and poured into a three-necked flask, and vigorously stirred at a temperature of 50-200°C for 1-12 hours to form a uniform PIMs / MOFs dispersion, wherein the molar concentration ratio of metal salt ions to PIMs in the MOFs seed solution is 0.05-1:1. Subsequently, the PIMs / MOFs dispersion is ultrasonically treated for 60-120 minutes to remove bubbles. Finally, the PIMs / MOFs dispersion is cast into an ultra-flat quartz disk and placed in an oven. After the solvent F is completely evaporated, the membrane is peeled off the quartz disk and immersed in methanol for 24-48 hours to eliminate residual metal salts and ligands. The obtained c-PIMs / MOFs composite membrane is vacuum dried.

[0029] The reaction mechanism of this step is: the polymer and MOFs seed solution are fully mixed and placed in a heating system, and the continuous evaporation of the solvent in the casting solution can concentrate the polymer chain. The confined space between the chains can limit the growth of MOF, promote the formation of small-sized MOFs fillers and enhance the interfacial compatibility between PIMs-MOFs. In addition, the growth site of MOFs can be anchored and its uniform distribution in the membrane can be promoted through the cross-linking reaction between MOF and the polymer matrix. The addition of MOFs can increase the selective permeation path of the gas in the membrane and improve the gas separation performance of the composite membrane. In this step: the present invention is based on the concept of solvent volatilization, and improves the gas separation performance and long-term stability of the PIMs composite membrane by optimizing the solvent volatilization conditions and regulating the interfacial compatibility between PIMs-MOFs. By regulating the evaporation rate of the solvent, the polymer and MOFs filler can form good contact at the phase interface, enhance the interaction, thereby improving the interfacial compatibility between PIMs-MOFs, effectively avoiding non-selective defects, and promoting the formation of defect-free composite membranes.

[0030] In the third step, the N2 purge rate is 5 to 30 L / min. The oven temperature is 30 to 120°C for 24 to 72 hours. The solvent F is one of N,N-dimethylformamide, N-methylpyrrolidone and chloroform. The vacuum drying temperature is 60 to 120°C for 24 to 72 hours.

[0031] The invention discloses an application of a uniformly distributed defect-free c-PIMs / MOFs composite membrane material for gas separation, salt difference power generation, ion exchange and other systems.

[0032] Beneficial effects of the present invention:

[0033] (1) The present invention uses a solvent evaporation method to construct a confined space between polymer chains to promote the uniform distribution of small-sized MOFs particles. Specifically: Under high temperature conditions, as the solvent in the PIMs-MOFs casting solution continues to evaporate, the confined space formed between the polymer chains limits the growth of MOFs, preventing them from aggregating into large particles, thereby promoting the formation of small-sized fillers. The dense polymer chain segments provide physical support for the MOFs particles, preventing them from settling to the bottom due to gravity. In addition, the cross-linking bonds between the PIMs chain segments and the MOFs particles help anchor the growth sites of the MOFs, further promoting the uniform dispersion of the MOFs particles in the polymer matrix.

[0034] (2) Improve the crystal growth efficiency of MOFs crystal particles in the membrane through MOFs pre-nucleation. Specifically: MOFs growth sites can be introduced into the PIMs-MOFs casting solution through MOFs pre-nucleation. In addition, by adjusting the pre-nucleation conditions, the growth rate of the crystal can be controlled, thereby improving the crystallinity and uniformity of MOFs in the PIMs-MOFs casting solution.

[0035] (3) Construction of defect-free PIMs-MOFs interface in the membrane. Specifically: By regulating the evaporation rate of the solvent, the polymer and MOFs filler can form good contact at the interface, enhance the interaction, thereby improving the interfacial compatibility between PIMs-MOFs, effectively avoiding non-selective defects, and promoting the formation of defect-free composite membranes.

[0036] (4) Functionalized MOFs have higher CO2 adsorption capacity. In addition, their unique microporous structure reduces the migration resistance of gas molecules in the membrane, further improving the gas separation performance of the composite membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a scanning electron microscope image of c-AOPIM / ZIF-90 of Example 1.

[0038] Figure 2 This is a scanning electron microscope image of c-PIM-COOH / UiO-66-NH2 of Example 2.

[0039] Figure 3 This is a scanning electron microscope image of c-SPIM-1 / HKUST-1 of Example 3.

[0040] Figure 4 This is a scanning electron microscope image of AOPIM / ZIF-90 of Comparative Example 1.

[0041] Figure 54 is the Fourier transform infrared spectra of c-AOPIM / ZIF-90, AOPIM-1 and ZIF-90 of Example 1.

[0042] Figure 6 It is a gas separation performance diagram of Examples 1 to 3 and Comparative Example 1. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the technical scheme of the present invention is described in detail below by the embodiments, but the protection scope of the present invention is not limited thereto.

[0044] Embodiment 1: The method of the present invention comprises the following steps:

[0045] Step 1: Preparation of modified polymer PIMs;

[0046] 1.1) Preparation of polymer PIM-1: Under N2 atmosphere, the reaction monomer TTSBI, TFTPN and anhydrous K2CO3 were dissolved in solvent A, and the mixture was poured into a three-necked flask and reacted at 65°C for 72 hours. After the reaction, the solution was cooled to room temperature and gradually poured into methanol to precipitate a fluorescent yellow solid. The obtained solid was dissolved in chloroform, and the solution was poured into methanol again for precipitation to obtain a polymer solid. This process was repeated several times to ensure the purity and quality of the polymer. The filtered polymer solid was poured into deionized water and stirred at 100°C for 4 hours to completely remove residual K2CO3. The collected yellow polymer was vacuum dried to obtain polymer PIM-1.

[0047] 1.2) Preparation of modified polymer PIMs;

[0048] The polymer PIM-1 obtained in step 1.1) was dissolved in solvent B under N2 atmosphere, and then the modified solution A was added to the reaction solution and refluxed at 65°C for 0.5h. After cooling to room temperature, the mixture was poured into solvent C and filtered to obtain a light yellow powder. The polymer product was washed with 500mL of ethanol for multiple times and then vacuum dried to obtain the modified polymer PIMs.

[0049] In the step 1.1), 4 g TFTPN and 6.91 g K2CO3 were added for every 7.36 g TTSBI in the step 1.1). The vacuum drying temperature was 60° C. and the time was 24 h.

[0050] In the step 1.1), the solvent A is N-methylpyrrolidone.

[0051] In the step 1.2), the solvent B is tetrahydrofuran; and the solvent C is a mixture of ethanol and deionized water.

[0052] In the step 1.2), the modified solution A is a hydroxylamine aqueous solution.

[0053] In the step 1.2), the modified polymer PIMs is AOPIM-1.

[0054] Step 2: Prepare MOFs seed solution;

[0055] 2.1) At room temperature, a metal salt is added to solvent D, and a uniform metal salt solution is formed by ultrasound at room temperature to prepare a metal salt dispersion with a concentration of 0.05 g / L; an organic ligand is added to solvent E, and a uniform organic ligand solution is formed by ultrasound at room temperature to prepare an organic ligand dispersion with a concentration of 0.05 g / L.

[0056] 2.2) Mix the metal salt dispersion and the organic ligand dispersion obtained in step 2.1), pour the reaction mixture into a three-necked flask, heat at 30°C for 24 hours, and cool naturally to room temperature to obtain a MOFs seed solution. For every 3 mL of the metal salt dispersion, 3 mL of the organic ligand dispersion is added.

[0057] In the step 2.1), the solvent D is N,N-dimethylformamide, and the solvent E is N,N-dimethylformamide.

[0058] In the step 2.1), the metal salt is zinc nitrate hexahydrate and the organic ligand is imidazole dicarboxaldehyde.

[0059] In the step 2.2), the MOFs is ZIF-90.

[0060] Step 3: Preparation of c-PIMs / MOFs composite membrane;

[0061] 3.1) The c-PIMs / MOFs composite membrane is thermally treated by a solvent evaporation method as follows:

[0062] Under N2 atmosphere, the ZIF-90 seed solution obtained in the second step and the AOPIM-1 obtained in the first step were dissolved in solvent F and poured into a three-necked flask, and stirred vigorously at 200°C for 1h to form a uniform AOPIM-1 / ZIF-90 dispersion, wherein the molar ratio of metal salt ions to PIMs in the MOFs seed solution was 0.05:1. Subsequently, the AOPIM-1 / ZIF-90 dispersion was ultrasonically treated for 60min to remove bubbles. Finally, the AOPIM-1 / ZIF-90 dispersion was cast into an ultra-flat quartz disk and placed in an oven. After the solvent F was completely evaporated, the membrane was peeled off the quartz disk and immersed in methanol for 24h to eliminate residual metal salts and ligands. The resulting composite membrane was vacuum dried and labeled as "c-AOPIM-1 / ZIF-90".

[0063] In the step 3.1), the N2 purge rate is 5 L / min.

[0064] In the step 3.1), the oven temperature is 120° C. and the time is 24 hours.

[0065] In the step 3.1), the solvent F is N,N-dimethylformamide, and the vacuum drying temperature is 120° C. and the time is 24 hours.

[0066] In Example 1, ZIF-90 crystals in the c-AOPIM-1 / ZIF-90 composite film are uniformly distributed in the AOPIM-1 matrix, the interface compatibility between the ZIF-90 crystals and the AOPIM-1 matrix is ​​good, and no non-selective defect holes appear. The size of the ZIF-90 nanoparticles is about 150nm, which indicates that the interchain confinement significantly limits the growth space of the ZIF-90 nanocrystals. In addition, the interaction between the amino groups in the AOPIM-1 segments and the aldehyde groups in the ZIF-90 promotes the uniform distribution of the ZIF-90 nanocrystals, achieving a defect-free c-AOPIM-1 / ZIF-90 composite structure.

[0067] Embodiment 2: The method of the present invention comprises the following steps:

[0068] Step 1: Preparation of modified polymer PIMs;

[0069] 1.1) Preparation of polymer PIM-1: Under N2 atmosphere, the reaction monomer TTSBI, TFTPN and anhydrous K2CO3 were dissolved in solvent A, and the mixture was poured into a three-necked flask and reacted at 120°C for 4 hours. After the reaction, the solution was cooled to room temperature and gradually poured into methanol to precipitate a fluorescent yellow solid. The obtained solid was dissolved in chloroform, and the solution was poured into methanol again for precipitation to obtain a polymer solid. This process was repeated several times to ensure the purity and quality of the polymer. The filtered polymer solid was poured into deionized water and stirred at 100°C for 4 hours to completely remove residual K2CO3. The collected yellow polymer was vacuum dried to obtain polymer PIM-1.

[0070] 1.2) Preparation of modified polymer PIMs;

[0071] The polymer PIM-1 obtained in step 1.1) was dissolved in solvent B under N2 atmosphere, and then the modified solution A was added to the reaction solution and refluxed at 155°C for 72h. After cooling to room temperature, the mixture was poured into solvent C and filtered to obtain a light yellow powder. The polymer product was washed with 500mL of ethanol for multiple times and then vacuum dried to obtain the modified polymer PIMs.

[0072] In the step 1.1), 6 g TFTPN and 10.37 g K2CO3 were added for every 7.36 g TTSBI in the step 1.1). The vacuum drying temperature was 90° C. and the time was 36 h.

[0073] In the step 1.1), the solvent A is N,N-dimethylformamide.

[0074] In the step 1.2), the solvent B is deionized water; the solvent C is deionized water.

[0075] In the step 1.2), the modified solution A is concentrated sulfuric acid.

[0076] In the step 1.2), the modified polymer PIMs is PIM-COOH.

[0077] Step 2: Prepare MOFs seed solution;

[0078] 2.1) At room temperature, a metal salt is added to solvent D, and a uniform metal salt solution is formed by ultrasound at room temperature to prepare a metal salt dispersion with a concentration of 1 g / L; an organic ligand is added to solvent E, and a uniform organic ligand solution is formed by ultrasound at room temperature to prepare an organic ligand dispersion with a concentration of 5 g / L.

[0079] 2.2) Mix the metal salt dispersion and the organic ligand dispersion obtained in step 2.1), pour the reaction mixture into a three-necked flask, heat at 120°C for 12 hours, and cool naturally to room temperature to obtain a MOFs seed solution. For every 3 mL of the metal salt dispersion, add 30 mL of the organic ligand dispersion.

[0080] In the step 2.1), the solvent D is N-methylpyrrolidone, and the solvent E is N-methylpyrrolidone.

[0081] In the step 2.1), the metal salt is zirconium chloride and the organic ligand is 2-aminoterephthalic acid.

[0082] In the step 2.2), the MOFs is UiO-66-NH2.

[0083] Step 3: Preparation of c-PIMs / MOFs composite membrane;

[0084] 3.1) The c-PIMs / MOFs composite membrane is thermally treated by a solvent evaporation method as follows:

[0085] Under N2 atmosphere, the UiO-66-NH2 seed solution obtained in the second step and the PIM-COOH obtained in the first step were dissolved in solvent F and poured into a three-necked flask. The mixture was stirred vigorously for 6 h at 100 °C to form a uniform PIM-COOH / UiO-66-NH2 dispersion, wherein the molar ratio of metal salt ions to PIMs in the MOFs seed solution was 0.3:1. Subsequently, the PIM-COOH / UiO-66-NH2 dispersion was ultrasonically treated for 90 min to remove bubbles. Finally, the PIM-COOH / UiO-66-NH2 dispersion was cast into an ultra-flat quartz disk and placed in an oven. After the solvent F was completely evaporated, the film was peeled off the quartz disk and immersed in methanol for 36 h to eliminate residual metal salts and ligands. The resulting composite film was vacuum dried and labeled as "c-PIM-COOH / UiO-66-NH2".

[0086] In the step 3.1), the N2 purge rate is 15L / min.

[0087] In the step 3.1), the oven temperature is 90° C. and the drying time is 48 hours.

[0088] In the step 3.1), the solvent F is N-methylpyrrolidone. The vacuum drying temperature is 90° C. and the time is 48 hours.

[0089] In Example 2, the UiO-66-NH2 crystals in the c-PIM-COOH / UiO-66-NH2 composite film are uniformly distributed in the PIM-COOH matrix, the interface compatibility between the UiO-66-NH2 crystals and the PIM-COOH matrix is ​​good, and no non-selective defect holes appear. The size of the UiO-66-NH2 nanoparticles is about 300nm, which indicates that the interchain confinement significantly limits the growth space of the UiO-66-NH2 nanocrystals. In addition, the interaction between the carboxyl groups in the PIM-COOH segments and the amino groups in UiO-66-NH2 promotes the uniform distribution of the UiO-66-NH2 nanocrystals, realizing a defect-free c-PIM-COOH / UiO-66-NH2 composite structure.

[0090] Embodiment 3: The method of the present invention comprises the following steps:

[0091] Step 1: Preparation of modified polymer PIMs;

[0092] 1.1) Preparation of polymer PIM-1: Under N2 atmosphere, the reaction monomer TTSBI, TFTPN and anhydrous K2CO3 were dissolved in solvent A, and the mixture was poured into a three-necked flask and reacted at 160°C for 0.5h. After the reaction, the solution was cooled to room temperature and gradually poured into methanol to precipitate a fluorescent yellow solid. The obtained solid was dissolved in chloroform, and the solution was poured into methanol again for precipitation to obtain a polymer solid. This process was repeated several times to ensure the purity and quality of the polymer. The filtered polymer solid was poured into deionized water and stirred at 100°C for 4h to completely remove residual K2CO3. The collected yellow polymer was vacuum dried to obtain polymer PIM-1.

[0093] 1.2) Preparation of modified polymer PIMs;

[0094] The polymer PIM-1 obtained in step 1.1) was dissolved in solvent B under N2 atmosphere, and then the modified solution A was added to the reaction solution and refluxed at 25°C for 9 hours. After cooling to room temperature, the mixture was poured into solvent C and filtered to obtain a light yellow powder. The polymer product was washed with 500 mL of ethanol for multiple times and then vacuum dried to obtain a modified polymer PIMs.

[0095] In the step 1.1), 8 g TFTPN and 13.82 g K2CO3 were added for every 7.36 g TTSBI in the step 1.1). The vacuum drying temperature was 120° C. and the time was 72 h.

[0096] In the step 1.1), the solvent A is N,N-dimethylacetamide.

[0097] In the step 1.2), the solvent B is dichloromethane; the solvent C is methanol.

[0098] In the step 1.2), the modified solution A is chlorosulfonic acid.

[0099] In the step 1.2), the modified polymer PIMs is SPIM-1.

[0100] Step 2: Prepare MOFs seed solution;

[0101] 2.1) At room temperature, a metal salt is added to solvent D, and a uniform metal salt solution is formed by ultrasound at room temperature to prepare a metal salt dispersion with a concentration of 3 g / L; an organic ligand is added to solvent E, and a uniform organic ligand solution is formed by ultrasound at room temperature to prepare an organic ligand dispersion with a concentration of 36 g / L.

[0102] 2.2) Mix the metal salt dispersion and the organic ligand dispersion obtained in step 2.1), pour the reaction mixture into a three-necked flask, heat at 140°C for 2 hours, and cool naturally to room temperature to obtain a MOFs seed solution. For every 3 mL of the metal salt dispersion, 60 mL of the organic ligand dispersion is added.

[0103] In the step 2.1), the solvent D is chloroform, and the solvent E is chloroform.

[0104] In the step 2.1), the metal salt is copper nitrate trihydrate and the organic ligand is trimesic acid.

[0105] In the step 2.2), the MOFs is HKUST-1.

[0106] Step 3: Preparation of c-PIMs / MOFs composite membrane;

[0107] 3.1) The c-PIMs / MOFs composite membrane is thermally treated by a solvent evaporation method as follows:

[0108] Under N2 atmosphere, the HKUST-1 seed solution obtained in the second step and the SPIM-1 obtained in the first step were dissolved in solvent F and poured into a three-necked flask. The mixture was stirred vigorously for 12 hours at 50°C to form a uniform SPIM-1 / HKUST-1 dispersion, in which the molar ratio of metal salt ions to PIMs in the MOFs seed solution was 1:1. Subsequently, the SPIM-1 / HKUST-1 dispersion was ultrasonically treated for 120 minutes to remove bubbles. Finally, the SPIM-1 / HKUST-1 dispersion was cast into an ultra-flat quartz disk and placed in an oven. After the solvent F was completely evaporated, the membrane was peeled off the quartz disk and immersed in methanol for 48 hours to eliminate residual metal salts and ligands. The resulting composite membrane was vacuum dried and labeled as "c-SPIM-1 / HKUST-1".

[0109] In the step 3.1), the N2 purge rate is 30 L / min.

[0110] In the step 3.1), the oven temperature is 30° C. and the drying time is 72 hours.

[0111] In the step 3.1), the solvent F is chloroform. The vacuum drying temperature is 60° C. and the time is 72 h.

[0112] In Example 2, the HKUST-1 crystals in the c-SPIM-1 / HKUST-1 composite film are uniformly distributed in the SPIM-1 matrix, the interface compatibility between the HKUST-1 crystals and the SPIM-1 matrix is ​​good, and no non-selective defect holes appear. The size of the HKUST-1 nanoparticles is about 500nm, which indicates that the interchain confinement significantly limits the growth space of the HKUST-1 nanocrystals. In addition, the interaction between the sulfonic acid groups in the SPIM-1 segments and the hydroxyl groups in HKUST-1 promotes the uniform distribution of the HKUST-1 nanocrystals, realizing a defect-free c-SPIM-1 / HKUST-1 composite structure.

[0113] Comparative Example 1: Comparison with Example 1, except that the preparation is not performed by solvent evaporation method, and other conditions are the same as those of Example 1.

[0114] The specific steps are as follows:

[0115] Step 1: Preparation of modified polymer PIMs;

[0116] 1.1) Preparation of polymer PIM-1: Under N2 atmosphere, the reaction monomer TTSBI, TFTPN and anhydrous K2CO3 were dissolved in solvent A, and the mixture was poured into a three-necked flask and reacted at 65°C for 72 hours. After the reaction, the solution was cooled to room temperature and gradually poured into methanol to precipitate a fluorescent yellow solid. The obtained solid was dissolved in chloroform, and the solution was poured into methanol again for precipitation to obtain a polymer solid. This process was repeated several times to ensure the purity and quality of the polymer. The filtered polymer solid was poured into deionized water and stirred at 100°C for 4 hours to completely remove residual K2CO3. The collected yellow polymer was vacuum dried to obtain polymer PIM-1.

[0117] 1.2) Preparation of modified polymer PIMs;

[0118] The polymer PIM-1 obtained in step 1.1) was dissolved in solvent B under N2 atmosphere, and then the modified solution A was added to the reaction solution and refluxed at 65°C for 0.5h. After cooling to room temperature, the mixture was poured into solvent C and filtered to obtain a light yellow powder. The polymer product was washed with 500mL of ethanol for multiple times and then vacuum dried to obtain the modified polymer PIMs.

[0119] In the step 1.1), 4 g TFTPN and 6.91 g K2CO3 were added for every 7.36 g TTSBI in the step 1.1). The vacuum drying temperature was 60° C. and the time was 24 h.

[0120] In the step 1.1), the solvent A is N-methylpyrrolidone.

[0121] In the step 1.2), the solvent B is tetrahydrofuran; and the solvent C is a mixture of ethanol and deionized water.

[0122] In the step 1.2), the modified solution A is a hydroxylamine aqueous solution.

[0123] In the step 1.2), the modified polymer PIMs is AOPIM-1.

[0124] Step 2: Prepare MOFs seed solution;

[0125] 2.1) At room temperature, a metal salt is added to solvent D, and a uniform metal salt solution is formed by ultrasound at room temperature to prepare a metal salt dispersion with a concentration of 0.05 g / L; an organic ligand is added to solvent E, and a uniform organic ligand solution is formed by ultrasound at room temperature to prepare an organic ligand dispersion with a concentration of 0.05 g / L.

[0126] 2.2) Mix the metal salt dispersion and the organic ligand dispersion obtained in step 2.1), pour the reaction mixture into a three-necked flask, heat at 30°C for 24 hours, and cool naturally to room temperature to obtain a MOFs seed solution. For every 3 mL of the metal salt dispersion, 3 mL of the organic ligand dispersion is added.

[0127] In the step 2.1), the solvent D is N,N-dimethylformamide, and the solvent E is N,N-dimethylformamide.

[0128] In the step 2.1), the metal salt is zinc nitrate hexahydrate and the organic ligand is imidazole dicarboxaldehyde.

[0129] In the step 2.2), the MOFs is ZIF-90.

[0130] Step 3: Preparation of PIMs / MOFs composite membrane;

[0131] 3.1) Heat treating the PIMs / MOFs composite membrane by solvent evaporation method, as follows:

[0132] Under N2 atmosphere, the ZIF-90 seed solution obtained in the second step and the AOPIM-1 obtained in the first step were dissolved in solvent F and poured into a sample bottle and stirred vigorously for 1 hour to form a uniform AOPIM-1 / ZIF-90 dispersion, wherein the molar ratio of metal salt ions to PIMs in the MOFs seed solution was 0.05:1. Subsequently, the AOPIM-1 / ZIF-90 dispersion was ultrasonically treated for 60 minutes to remove bubbles. Finally, the AOPIM-1 / ZIF-90 dispersion was cast into an ultra-flat quartz disk and placed in an oven. After the solvent F was completely evaporated, the membrane was peeled off the quartz disk and immersed in methanol for 24 hours. The resulting composite membrane was vacuum dried and labeled "AOPIM-1 / ZIF-90".

[0133] In the step 3.1), the N2 purge rate is 5 L / min.

[0134] In the step 3.1), the oven temperature is 120° C. and the time is 24 hours.

[0135] In the step 3.1), the solvent F is N,N-dimethylformamide, and the vacuum drying temperature is 120° C. and the time is 24 hours.

[0136] In Comparative Example 1, the ZIF-90 crystals in the AOPIM-1 / ZIF-90 composite membrane are mainly distributed at the bottom of the AOPIM-1 matrix, and the size of the ZIF-90 nanoparticles is about 1 μm. This indicates that in the low-viscosity casting solution, the sparsely arranged polymer segments are difficult to support the nanoparticles, so the large-sized ZIF-90 are all deposited to the bottom of the composite membrane under the action of gravity.

[0137] The c-PIMs / MOFs composite membrane prepared in the above embodiment was subjected to CO2, N2, and CH4 flux tests, and the results are shown in the following table:

[0138] Table 1. Gas separation performance of examples and comparative examples

[0139]

[0140] It can be seen from the data in Table 1 that the c-PIMs / MOFs composite membrane obtained by the present invention has good gas separation performance. Comparing Examples 1-3 treated by the solvent evaporation method with Comparative Example 1 that has not been treated by the solvent evaporation method, it can be seen that the flux of CO2 in Examples 1-3 is above 1509.48 Barrer, which is a certain improvement compared to Comparative Example 1. This is because the uniform distribution of MOFs in the composite membrane provides a rapid gas transmission path, making it easier for gas molecules to pass through the composite membrane. The ideal selectivity of CO2 / N2 and CO2 / CH4 in Examples 1-3 increased by nearly 1.3-3.6 times relative to Comparative Example 1. This is because after the solvent evaporation treatment, the interfacial compatibility between MOFs nanoparticles and the polymer matrix is ​​improved, reducing interfacial defects, which helps to improve the selective permeation of gas molecules. The combination of solvent evaporation and MOFs anchoring growth can construct confinement between polymer segments, thereby avoiding excessive growth of MOFs crystals and prompting them to form smaller nanoparticles, which helps to reduce interfacial defects in the membrane. The interaction between MOFs particles and polymer segments effectively anchors the growth sites of MOFs and promotes the uniform distribution of MOFs particles in the membrane. In addition, the microporous structure of MOFs in the membrane provides additional gas-selective transmission channels, significantly improving the separation efficiency of CO2 gas. It can be seen that this improved solvent evaporation method, as a synthetic technology, has significant potential for constructing uniformly distributed defect-free separation membranes in a variety of polymers.

[0141] This method is based on the concept of solvent evaporation. By optimizing the solvent evaporation conditions and regulating the interfacial compatibility between PIMs-MOFs, the gas separation performance and long-term stability of the PIMs composite membrane are improved. Under high temperature, as the solvent in the PIMs-MOFs casting solution continues to evaporate, the confined space formed between the polymer chains restricts the growth of MOFs, preventing them from aggregating into large particles, thereby promoting the formation of small-sized fillers. The dense polymer segments provide physical support for MOFs particles, preventing them from settling to the bottom due to gravity. MOFs growth sites can be introduced into the PIMs-MOFs casting solution through MOFs prenucleation. In addition, by adjusting the prenucleation conditions, the growth rate of the crystal can be controlled, thereby improving the crystallinity and uniformity of MOFs in the PIMs-MOFs casting solution. The cross-linking bonds between the PIMs segments and the MOFs particles help anchor the growth sites of MOFs, further promoting the uniform dispersion of MOFs particles in the polymer matrix. By regulating the evaporation rate of the solvent, the polymer and MOFs filler can form good contact at the phase interface, enhance the interaction, and thus improve the interfacial compatibility between PIMs-MOFs, effectively avoid non-selective defects, and promote the formation of defect-free composite membranes. Therefore, the defect-free PIMs-MOFs cross-linked structure provides a mass transfer path for efficient gas separation in the composite membrane, realizes the selective and rapid transfer of gas, and further realizes the preparation of uniformly distributed defect-free composite membranes.

[0142] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the patent scope of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A uniformly distributed defect-free c-PIMs / MOFs composite membrane, characterized in that: The composite membrane is a homogeneous membrane, comprising a modified PIMs matrix and MOFs nanoparticles, wherein the MOFs nanoparticles are uniformly embedded in the modified PIMs matrix, and are specifically composed of a modified PIMs segment structure, and a MOFs and PIMs cross-linked structure; in the composite membrane, there are continuous cavities in the PIMs matrix and regular channels in the MOFs.

2. The uniformly distributed defect-free c-PIMs / MOFs composite membrane according to claim 1, characterized in that: The thickness of the c-PIMs / MOFs composite membrane material is 50-150 μm.

3. A method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane according to claim 1 or 2, characterized in that: The preparation method first prepares modified polymer PIMs; secondly, prepares a MOFs seed solution; finally, heat-treats the PIMs / MOFs casting solution by a solvent volatilization method to construct a confined space between polymer chains to regulate the growth space and distribution state of MOFs, and prepares a c-PIMs / MOFs composite membrane; the formula of the casting solution of the composite membrane contains modified PIMs, MOFs nanoparticles and a solvent.

4. The method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane according to claim 3, characterized in that: The following steps are involved: Step 1: Preparation of modified polymer PIMs; Step 1.1) preparing polymer PIM-1: under an inert atmosphere, dissolving reaction monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane TTSBI, tetrafluoroterephthalonitrile TFTPN and anhydrous potassium carbonate K2CO3 in solvent A, reacting at a temperature of 65 to 160° C. for 0.5 to 72 h, and performing post-treatment after the reaction to obtain polymer PIM-1; Step 1.2) preparing modified polymer PIMs; The polymer PIM-1 obtained in step 1.1) is dissolved in solvent B under an inert atmosphere, and then the modified solution A is added, and refluxed at 25-155° C. for 0.5-72 h; after cooling to room temperature, the mixture is poured into solvent C to obtain a light yellow powder, which is vacuum dried to obtain a modified polymer PIMs; Step 2: Prepare MOFs seed solution; Step 2.1) adding a metal salt to a solvent D at room temperature to prepare a metal salt dispersion having a concentration of 0.05 to 3 g / L; Adding the organic ligand into solvent E to prepare an organic ligand dispersion having a concentration of 0.05 to 36 g / L; Step 2.2) After mixing the metal salt dispersion and the organic ligand dispersion obtained in step 2.1), heating at 30-140° C. for 2-24 hours, and naturally cooling to room temperature to obtain a MOFs seed solution; 3-60 mL of the organic ligand dispersion is added to each 3 mL of the metal salt dispersion; Step 3: heat treat the c-PIMs / MOFs composite membrane by solvent evaporation method, as follows: Under an inert atmosphere, the MOFs seed solution of the second step and the modified polymer PIMs of the first step are dissolved and mixed, and vigorously stirred at a temperature of 50-200°C for 1-12 hours to form a uniform PIMs / MOFs dispersion and ultrasonically treated, wherein the molar concentration ratio of metal salt ions to PIMs in the MOFs seed solution is 0.05-1:1; the PIMs / MOFs dispersion is used as a casting liquid for casting and oven drying, and the membrane is peeled off after the solvent F is completely evaporated, and vacuum dried to obtain a c-PIMs / MOFs composite membrane.

5. The method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane according to claim 4, characterized in that: In the first step described: In the step 1.1), 4-8 g TFTPN and 6.91-13.82 g K2CO3 are added for every 7.36 g TTSBI; In the step 1.2), the solvent B is one of tetrahydrofuran, deionized water, and dichloromethane; the modified solution A is one of hydroxylamine aqueous solution, concentrated sulfuric acid, and chlorosulfonic acid; In the step 1.2), the modified polymer PIMs obtained is one of amidoximated PIMs (AOPIM-1), carboxylated PIMs (PIM-COOH), and sulfonated PIMs (SPIM-1).

6. The method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane according to claim 5, characterized in that: When solvent B is tetrahydrofuran and modification solution A is aqueous hydroxylamine solution, the modified PIMs obtained are AOPIM-1; when solvent B is deionized water and modification solution A is concentrated sulfuric acid, the modified PIMs obtained are PIM-COOH; when solvent B is dichloromethane and modification solution A is chlorosulfonic acid, the modified PIMs obtained are SPIM-1.

7. The method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane according to claim 4, characterized in that: In the second step: In the step 2.1), the metal salt is one of zinc nitrate hexahydrate, zirconium chloride, and copper nitrate trihydrate; the organic ligand is one of imidazole dicarboxaldehyde, 2-aminoterephthalic acid, and trimesic acid; In the step 2.2), the MOFs in the obtained seed solution is one of ZIF-90, UiO-66-NH2, and HKUST-1.

8. The method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane according to claim 7, characterized in that: In the step 2.2), when the metal salt is zinc nitrate hexahydrate and the organic ligand is imidazole dicarboxaldehyde, the obtained MOFs is ZIF-90; when the metal salt is zirconium chloride and the organic ligand is 2-aminoterephthalic acid, the obtained MOFs is UiO-66-NH2; when the metal salt is copper nitrate trihydrate and the organic ligand is trimesic acid, the obtained MOFs is HKUST-1.

9. The method for preparing a uniformly distributed defect-free c-PIMs / MOFs composite membrane according to claim 4, characterized in that: In the step 1.1), the solvent A is one of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide; the vacuum drying temperature is 60-120° C. and the time is 24-72 hours; In the step 1.2), the solvent C is one or more of deionized water, methanol, and ethanol; The post-treatment process in step 1.1) is as follows: cooling the reaction solution to room temperature, pouring methanol into it to obtain a precipitate, dissolving the precipitate, and then pouring methanol into it to get out the precipitate, repeating this process several times, and filtering to obtain a polymer solid; pouring it into deionized water, stirring, filtering, and vacuum drying to obtain a polymer PIM-1; In the step 2.1), the solvent D is one of N,N-dimethylformamide, N-methylpyrrolidone and chloroform, and the solvent E is one of N,N-dimethylformamide, N-methylpyrrolidone and chloroform; In the third step, the N2 purge rate is 5 to 30 L / min; the oven drying temperature is 30 to 120°C, and the time is 24 to 72 hours; the solvent F is one of N,N-dimethylformamide, N-methylpyrrolidone, and chloroform; the vacuum drying temperature is 60 to 120°C, and the time is 24 to 72 hours.

10. An application of the uniformly distributed defect-free c-PIMs / MOFs composite membrane according to claim 1 or 2, characterized in that: Used for gas separation, salt difference power generation, and ion exchange systems.

Citation Information

Patent Citations

  • Preparation method of PIM-1@MOFs / polymer composite pervaporation membrane

    CN110026097A

  • MOF / PIM-1 in-situ crosslinked matrix membrane and preparation method thereof

    CN110433668A

  • Novel C2NxO1-x / PIM-1 mixed matrix membrane and preparation method and application thereof

    CN113578068A

Cited By

  • Preparation method of defective MOF (Metal Organic Framework)-based intrinsic microporous polymer mixed matrix membrane for efficient separation of propylene and propane

    CN119819139A